A blind insertion airway device in dogs as an alternative to traditional endotracheal intubation. Issue 2 (February 2015) - James, Timothy; Lane, Michael; Crowe, Dennis; Pullen, William
Highlights A blind insertion airway device provides adequate ventilation for medium to giant breed dogs. It is not a suitable replacement for traditional endotracheal intubation. The device could be considered for use in emergency situations. The blind insertion airway device may be used when traditional endotracheal intubation is not feasible.